Impact of inter-pregnancy interval on long-term endo-metabolic health of the offspring - Liron, Seidman; Tamar, Wainstock; Eyal, Sheiner; Gali, Pariente; Ruslan, Sergienko; Asnat, Walfisch (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: